Determination of Folic Acid in Multivitamin Preparations by Reversed Phase HPLC - A. S. Alekseeva; M. V. Gavrilin; T. B. Shemeryankina; M. S. Smirnova; E. P. Fedorova; T. M. Kargina; O. O. Novikov; S. A. Kovaleva; N. N. Boyko (Регуляторные исследования и экспертиза лекарственных средств)
A great variety of components in multivitamin preparations containing folic acid, and a variety of test methods and conditions of folic acid determination proposed by manufacturers, require alignment of test procedures for products with similar composition.The aim of the study was to compare the results of experimental verification of folic acid determination procedures which use reversed phase high-performance liquid chromatography (RP HPLC) with isocratic elution mode. Materials and methods: The Agilent 1260 Infinity II LC system with a diode array detector (280 nm), isocratic elution mode, C8- and C18-bonded silica gel chromatographic columns, model mixtures containing folic acid, cyanocobalamin, ferrous sulfate, and potassium iodide, were used in the study.Results: The lowest relative standard deviation of the folic acid peak area (RSD=0.09%), and the lowest asymmetry factor (As=1.04) for folic acid were observed for the model mixture “ferrous sulfate+folic acid+cyanocobalamin” and the following test conditions. Column: 250×4.0 mm, silica gel for chromatography, octylsilyl (C8), endcapped; mobile phase:  methanol‒phosphate buffer (12:88), pH 6.6; column temperature: 25ºС. The study demonstrated the feasibility of using these conditions for determination of pteroic acid impurity with simultaneous precipitation of interfering ferrous ions, using ethylenediaminetetraacetic acid solution, pH 9.5, as a solvent.Conclusions: RP HPLC can be recommended as an optimal aligned test procedure for determination of folic acid in combination products. It is recommended to use a solution containing folic and pteroic acids for system suitability testing.